Pengaruh Diferensiasi Produk dan Harga terhadap Minat Beli pada Sepeda Fixie di Kota Padang - Susanto, Perengki; Rahmi, Nella (Jurnal Kajian Manajemen Bisnis, 2013)
The purpose of this research is to determine the extent of the impact of product differentiation and price towards intention to buy on Fixie bike in Padang. The populations in this study are all the people of Padang who were aged 15-24 years which have known Fixie bike but have never had a Fixie. The sample of 100 respondents which used the sampling technique using proportionate stratified random sampling method. The primary data in this study were obtained from questionnaires distributed to the respondents, while secondary data is data associated with the object of the research presented by the other party. Data analysis techniques using descriptive analysis and inductive analysis using multiple linear regression analysis techniques. Hypotheses were tested by t test at Î± = 0.05. The results showed that the product differentiation significantly influence intention to buy on Fixie bikes in Padang as evidenced by the results of the t test of 4.147 is greater than t table (1.98472) or with sig 0.000 <0.05. Furthermore, prices have a significant effect towards intention to buy on Fixie bikes in Padang as evidenced by the results of the t test of 3.441 is greater than t table (1.98472) or with sig 0.001 <0.05. Obtained R-square value of 0.374, which means that the dependent variable is explained by the independent variables at 37.4% while the remaining 62.6% is explained by other variables outside the model.